FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI - Rondonuwu, Rolly Harvie Stevan; Lestari, Dwi; Mudhofar, Muhamad Nor; Hikmah, Raudatul; Tatisina, Cut Mutia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Hypertension is a serious medical condition and can increase the risk of heart, brain, kidney and other diseases. The results of the initial survey, it is known that based on medical record data in 2022, there were 91 patients with hypertension at Grestelina Hospital. While in 2023 there was an increase of 208 patients. The purpose of the study was to determine the factors associated with the incidence of hypertension. This type of research is quantitative with a cross sectional approach. The research was conducted at the Grestelina Hospital Polyclinic room in November 2023. The sample amounted to 24 people using accidental sampling. Data analysis was carried out univariate and bivariate. The results showed that there was a relationship between age (p value: 0.003) and lifestyle (p value: 0.024) on the incidence of hypertension. It is recommended that hypertensive patients pay more attention to health conditions by implementing a healthy lifestyle regularly and the family or the closest person to the patient motivates the patient to always maintain health by helping to manage a regular lifestyle.Keywords: Hypertension, Lifestyle, Age.